Future of Health Services: The Role of Physicians in the Disruptive Era - Budi Wiweko; Sarah Chairani Zakirah (Wolters Kluwer Medknow Publications, 2020)
This article aimed to address the role of physicians in future health in the disruptive era. Physicians in this disruptive era must increase their capability and knowledge to compensate for this development. Advances in technology increase the impact on health care and the significance of disruption. Disruptive innovation encompasses several fields, such as physics, digital, and biology. Big data as one of the most important parts in clinical aspects encompass high-throughput cellular and protein-binding assays toward chemoinformatic-driven databases. Health status can be modified by changing epigenetic factor, such as lifestyle and environment. As a result, they affect human genetics and provide the insight of pathophysiology of disease, clinical treatment, and early preventive action. Disruptive innovations in health-care align with the development of artificial intelligence, machine learning, robotics, Internet of things, digitalization, and genomics. New paradigm shifting in physician-patient relationships is relevant to consumer health informatics.